Lyrical business plan - Oliver Moltgen, Erik (2018)
This paper looks to form a comprehensive business plan elaborating the rationale, design, and implementation approach of spinning-off the existing influencer marketing capability within Dentsu Aegis Network into a stand-alone brand and business entity: Lyrical Snd Bhd.